Audit Pricing in China and Pakistan: A Comparative Review of Audit Practices - Zahid Irshad Younas; Patrick Velte; Khadija Ashfaq (Journal of Accounting and Management Information Systems (JAMIS), 2014)
The purpose of this study is to investigate the firm-level factors effect on the audit pricing in China and Pakistan. For this purpose, we used the panel data of 160 firms of each country of study for the period from 2005 to 2011. First, we run the combined model for two countries and observed that complexity of business transaction is the only variable contributing positively and significantly in audit pricing of both countries. Then, for comparative review, we segregated the data of each country and run separate model. The results of separate models show that, in the case of Pakistan auditors mainly consider complexity of business transactions and client risk while pricing their engagement as an auditor. However, in the case of China the auditors only consider the Big 4 audit firm effect as a reputational tool while pricing their audit activity. The auditors in China totally ignore the client risk and complexity of business transactions which may be problematic for their auditing firm in future. The study concludes that audit pricing in Pakistan is more rational in comparison to China.
Keywords: M41; M42; 650; audit pricing; corporate governance; client risk; big 4 audit firms; audit quality